Minimally Invasive Mapping Guided Surgical Treatment of Atrial Fibrillation. Utopia or Near Future? - van Brakel, Thomas J (Indian Pacing and Electrophysiology Group, 2006)
Isolation of the pulmonary veins has been used as surgical treatment for atrial fibrillation (AF) from the early 90s, as it was incorporated in the Maze procedure. With the evidence that triggers form this area can induce AF, the Maze III procedure has been adapted and modified towards a single lesion around the pulmonary veins for the treatment of paroxysmal and chronic AF in some centers. New ablation techniques with a diversity of energy sources further paved the way for less invasive procedures. Minimal invasive techniques to prevent major surgery may potentially make the treatment available for a patient population that do not have to undergo cardiac surgery for other reasons. Besides these technical developments, high density mapping can be used to identify the AF substrate in the individual patient and optimization of the treatment by local substrate guided ablation. This review aims to summarize the robotic and thoracoscopic techniques to isolate the pulmonary veins. Furthermore, it is discussed why pulmonary veins isolation may be effective in patients with chronic AF, and whether there is a role for mapping guided minimal invasive surgical treatment of AF in the near future.